2020
DOI: 10.21203/rs.3.rs-127179/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parental Experiences in Neonatal Intensive Care Unit at Felege Hiwot Comprehensive Specialized Hospital, Bahir Dar, Ethiopia: A Phenomenological Study

Abstract: Background: Neonatal intensive care settings are important to save the lives of sick neonates; however, parents are challenged by many stressful conditions during their stay outside the rooms of intensive care units. Therefore, this study aimed to explore the lived experiences of parents in a neonatal intensive care unit at Felege Hiwot Comprehensive Specialized Hospital, Bahir Dar, Northwest Ethiopia. Methods: In this study, a phenomenological qualitative approach was used to explore parental experience and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The respondents' level of education was found to be inversely associated with the level of satisfaction, as already reported by other authors (12,41). This might indicate that parents with a higher level of education have a greater expectations regarding the quality of care provided to their newborn.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The respondents' level of education was found to be inversely associated with the level of satisfaction, as already reported by other authors (12,41). This might indicate that parents with a higher level of education have a greater expectations regarding the quality of care provided to their newborn.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, it has been shown that place of residence might influence satisfaction, whereby people living in rural areas tend to be more satisfied compared to those living in urban areas (12,41). Levels of parent satisfaction in Care and Treatment for their children were also found to be lower for longer lengths of hospital stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies conducted in Bahirdar in Ethiopia, Ghana, South Africa, Botswana and Jordan reported that although the healthcare providers were supportive and appreciative of their support, some mothers perceived that some of the nurses were unfriendly, and they expressed having had bad experiences with NICU staff where the nurses lacked discipline, commitment, interest, and were not cooperative to support them, which increased mothers' anxiety and frustration. 11,16,25,29,30 This implies that there is a gap which should be taking into consideration that the HCPs should communicate effectively to understand their situation. https://doi.org/10.2147/RRN.S417173…”
Section: Discussionmentioning
confidence: 99%
“…And also, they were concerned and worried about the financial aspect of care in the NICU. 11,24,29,32,33 This might be because mothers spend a long time in the hospital and often do not get medicine and other laboratory tests in the hospital, instead purchasing them from private pharmacies and clinics. If the medication issue is resolved, mothers will be relieved of the financial burden of medication costs.…”
Section: Dovepressmentioning
confidence: 99%